2014
DOI: 10.1159/000370136
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Specificity of Red Blood Cell Alloimmunization in Chilean Transfused Patients

Abstract: Background: Alloimmunization is an adverse effect of blood transfusions. In Chile, alloimmunization frequency is not established, and for this reason the aim of this study was to investigate the prevalence and specificity of red blood cell (RBC) alloantibodies in Chilean transfused subjects. Methods: Records from 4,716 multi-transfused patients were analyzed. In these patients, antibody screening was carried out prior to cross-matching with a commercially available two-cell panel by the microcolum gel test, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
8
2
Order By: Relevance
“…They also found that most alloimmunised patients (53·5%) produced only one type of alloantibody, which corroborates with the results found in our study. Additionally, in a more recent study, the incidence of RBC alloimmunisation in transfused individuals was similar to those found in our study (Caamano et al, ). However, these results differ from those of other studies that identified a higher frequency of patients with more than one type of alloantibody (Blumberg et al, ; Fluit et al, ; Schonewille et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…They also found that most alloimmunised patients (53·5%) produced only one type of alloantibody, which corroborates with the results found in our study. Additionally, in a more recent study, the incidence of RBC alloimmunisation in transfused individuals was similar to those found in our study (Caamano et al, ). However, these results differ from those of other studies that identified a higher frequency of patients with more than one type of alloantibody (Blumberg et al, ; Fluit et al, ; Schonewille et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies reported that alloimmunization is more likely in patients who receive more units of blood[ 9 18 ] while others found no significant association between alloantibodies formation and the number of transfused packed RBCs. [ 19 ] In our study, the association of development of alloimmunization and the number of units transfused were not statistically significant ( P = 0.117).…”
Section: Discussioncontrasting
confidence: 57%
“… 20 The specificity of RBC alloantibodies varies according to the study population. In Japan, anti-Rh antigens (E, c) and anti-Lewis (Lea) are the most prevalent 4 ; in India and China, anti-Rh (E, D) and anti-MNS (M) 6 , 22 ; in Korea, anti-Lewis (Lea) 28 ; in Chile, anti-Rh (D, E) and anti-Kell (K) 29 ; and in Iran, anti-Kell (K). 30 …”
Section: Discussionmentioning
confidence: 99%